Pakaian Muslimah dalam Perspektif Hadis dan Hukum Islam - Arifuddin, Anshar (DIKTUM: Jurnal Syariah dan Hukum, 2019)
Human who has common sense and perfect mind, want to look attractive, whether Islamic or social norms prevailing in general society. Indonesian society which predominantly Islam, should understand how to dress decently according to their teachings. But, lately, there are found many muslimah do not dress with the rules and the teachings of Islamic religion. Good dressing habits should be instilled early to sake muslimah toda accustomed by syariah dressing and to make islamic dress code entrenched in society. The focus of this article is to know about the prosedure and etiquette of a Muslimah‘s dressing according to shariah. This study take a conclusion that In brief, through the lenses of The Prophet’s hadiths, Muslimah should cover every parts of their bodies except for their face and palms of their hands, dress up loosely, avoid dressing similarly with males, avoid dressing up excessively that attracts attention and shows arrogance.